Effects of electrostatic particle ionization on air quality, emissions, and growth performance of pigs housed in a thermo-regulated facility - Jon A De Jong; Korrin N Card; Joel M DeRouchey; M Baumgartner; Peter J Tomlinson (Kansas Agricultural Experiment Station Research Reports, 2014)
Two identical 200-head nurseries at the Kansas State University Segregated Early Weaning Facility were used for 5 consecutive all-in, all-out groups to determine the effect of electrostatic particle ionization (EPI) on air quality, emissions, and growth performance of pigs housed in a thermo-regulated facility. During five 6-wk periods (13 to 51 lb BW), the EPI system was used in one barn for a complete group and then used in the other barn for the next group. At the beginning of each 6-wk trial period, pigs were randomly allotted to pens based on average pig weight. Air measurements and pig growth were measured every week throughout the studies. Overall, when active, the EPI system reduced (P<0.05) 0.3, 0.5, 1.0, 2.5, 5.0, and 10.0 Î¼ dust particles in the barn and dust particles/ft3 at the exhaust fan. There were no differences (P>0.10) for in-barn air ammonia and hydrogen sulfide concentrations and no significant differences (P>0.10) in ammonia concentrations in the dust between the control and EPI barn. The EPI system tended to improve (P = 0.09) ADG, which led to a tendency for improved (P = 0.06) final BW. No differences were detected (P>0.10) for ADFI or F/G. The EPI system improved barn and exhaust air by removing particulate matter from suspension, which tended to improve growth rate in 13- to 51-lb pigs.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Dust; Electrostatic particle ionization; Emissions; Growth; Nursery pig